A mixed media approach using locally available neutralizing materials for the passive treatment of acid mine drainage - Joshua Pocaan; Casey Oliver A. Turingan; Carlito Baltazar Tabelin; Joshua B. Zoleta; Takahiko Arima; Ilhwan Park; Mayumi Ito; Aileen H. Orbecido (Heliyon, 2025)
Acid mine drainage (AMD) is generally managed via active or passive treatment strategies. Between the two, passive treatment is explored as a more sustainable alternative, especially for abandoned and legacy mines due to their low energy, manpower and material requirements. Recent studies of the authors have explored the use of limestone and waste materials like low-grade ores (LGO), fly ash (FA), and concrete wastes (CW) for AMD treatment and found that although these materials generated alkalinity individually, they could only partially remove sulfate (SO42−) and some heavy metals. To address this limitation, a mixed media approach using these four materials is proposed to neutralize the pH of AMD and maximize metal and SO42− removal. A total of twenty (20) mixtures of the four materials were identified based on the response surface methodology (RSM) experimental design. Laboratory-scale experiments using simulated AMD were performed to assess the performance of each mixture by monitoring the pH, oxidation-reduction potential (Eh), electrical conductivity (EC), and concentrations of metals and SO42−. Based on the results, three optimized mixed media compositions were identified. Overall, simulated AMD passively treated by the optimized mixed media compositions met the Philippine effluent standards except for SO42−.